Nahiye of Vučitrn in the 15th and 16th Centuries - Katić, Tatjana M.; Šešum, Uroš S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper seeks to determine the number of settlements in the Vučitrn nahiye (area, administrative unit) in the 15th and 16th centuries, their geographical position and population dynamics. Based on the Ottoman archival documents, tapu tahrir defters of the Vučitrn sancak, especially the one from 1570 or 1571, the scope of the Vučitrn nahiye was established as well as the list of inhabited places, abandoned villages, mezras, and the most important monasteries. The majority of the 188 inhabited villages of the nahiye which appear in the Ottoman cadastral census from 1570/1571, were detected with the help of lexicographical sources, anthropogeographical works, and travel literature from the 19th century or based on preserved names in microtoponymy and material traces on site, thus enabling the mapping of settlements and drawing the boundaries of the nahiye. However, some old villages could not be located because they merged with other settlements, changed their names or did not leave any trace on the terrain or in the folk memory.Identification of the disappeared settlements was made difficult or impossible by the consequences of lively migration processes, epidemics of infectious diseases, wars, and riots between the 16th and the beginning of the 20th century, but certainly most of all by the changes in the ethnic structure of the abovementioned area. Namely, judging by the onomastics in the Ottoman defters from the 15th and 16th centuries, the Serbs were the predominant, if not the only Christian population, in the Vučitrn area. A small number of Muslims, whose ethnic origins were not possible to establish, were counted in 50 villages. In many cases, however, these were probably those who only owned land in the settlements but did not live there. By the end of the 16th century and later, the Albanian population started to inhabit the nahiye of Vučitrn, especially during and after the Ottoman-Habsburg wars at the end of the 17th and 18th centuries. In the same period, the emigration of Serbs took place, which finally led to a more dominant presence of Albanians in some parts of today’s Kosovo and Metohija. The most profound ethnic changes happened in the 19th century, after the Serbian-Ottoman war in 1877–1878, when completely new Albanian, Circassian, and Bosnian Muslim villages were founded in the area of Vučitrn, Priština, and Gnjilane.
Keywords: Sancak of Vučitrn; Ottoman cadastral surveys; Vuk Branković’s land